Design Thinking: Interior Architecture and Interior Design in Thailand - Charlie Maturakarn; Chumporn Moorapun (My University, 2017)
This research aims to explore the aspects of design thinking of students from two different curricula: Interior Architecture (five years) and Interior Design (four years) to see what different aspects of design thinking. The research method is a survey based on quantitative approach. A questionnaire is developed from Perry scheme of intellectual development and Kolb’s Experiential Learning Theory (ELT) model. Then, both aspects were compared to see the difference. The findings indicate that the pattern of design thinking and learning style from two curricula are different and can be improved the thinking and learning styles of design students in Thailand.
Keywords: Learning design; Creativity in Education and Neuroscience